Analisis Kepuasan Penggunaan Vendor Management System iVendor PT. Pertamina (Persero) Menggunakan Metode TAM dan EUCS - Rizal, Ahmad; Mustikasari, Metty (Jurnal Ilmiah Matrik, 2024)
Information technology has significantly changed a variety of life, including corporate buying. The iVendor Pertamina vendor management system is a technological innovation that was created to manage procurement effectively. There are still problems influencing customer satisfaction even with its enhanced functionality and usability. The purpose of this study is to determine the variables that affect users' satisfaction with the iVendor system and to offer suggestions for enhancements. The End-User Computing Satisfaction (EUCS) and Technology Acceptance Model (TAM) research models are employed. 95 PT Pertamina (Persero) active iVendor users received questionnaires as part of the quantitative study approach. Results show that perceived usefulness, accuracy, and attitude toward use have a significant impact on user satisfaction. Perceived ease of use, content, format, timeliness, and ease of use do not significantly affect the attitude toward using. The conclusion is that factors such as perceived usefulness and information accuracy have a significant impact on user satisfaction with the iVendor system. To enhance user satisfaction, the study recommends improving the information quality and usability of the iVendor system.